Barotropic seiches in a perennially ice‐covered lake, East Antarctica. Issue 1 (16th December 2021) - Castendyk, Devin N.; Dugan, Hilary A.; Gallagher, Hugh A.; Pujara, Nimish; Doran, Peter T.; Priscu, John C.; Lyons, W. Berry
Abstract: Water movement in ice‐covered lakes is known to be driven by wind, sediment heat flux, solar radiation, saline density flows, and advective stream discharge. In large ice‐covered lakes, wind‐induced oscillations have been found to play a major role in horizontal flows. Here, we report recurrent, wind‐driven, barotropic seiches in a small lake with a thick ( 4 m) permanent ice‐cover. Between 2010 and 2016, we recorded 10.5‐ to 13‐min oscillations of the hydrostatic water level in Lake Hoare, McMurdo Dry Valleys, East Antarctica, using pressure transducers moored to the lake bottom and suspended from the ice cover. Theoretical calculations showed a barotropic seiche should have a period of 12.6 min. Barotropic seiches were most frequent during high wind events (> 5 m s −1 ) in winter months (February–November). The period increased during summer months (December–January) when fast ice thinned and melted along the shoreline.